2016
DOI: 10.1021/acs.langmuir.6b00553
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and Reversible Assembly of Extracellular-like Matrix by Enzyme-Active Colloidosome-Based Protocells

Abstract: The secretion and reversible assembly of an extracellular-like matrix by enzyme-active inorganic protocells (colloidosomes) is described. Addition of N-fluorenyl-methoxycarbonyl-tyrosine-(O)-phosphate to an aqueous suspension of alkaline phosphatase-containing colloidosomes results in molecular uptake and dephosphorylation to produce a time-dependent sequence of supramolecular hydrogel motifs (outer membrane wall, cytoskeletal-like interior and extra-protocellular matrix) that are integrated and remodelled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…259 The authors also observed the formation of nanofilaments from the hydrogels which were further investigated in a subsequent study. 260 A primitive cell-like division process of silica protocells was also invented by Mann and co-workers. Here, colloidal capsules containing a sodium phosphate buffer solution in a continuous oil phase were produced.…”
Section: Inorganic Protocellsmentioning
confidence: 99%
“…259 The authors also observed the formation of nanofilaments from the hydrogels which were further investigated in a subsequent study. 260 A primitive cell-like division process of silica protocells was also invented by Mann and co-workers. Here, colloidal capsules containing a sodium phosphate buffer solution in a continuous oil phase were produced.…”
Section: Inorganic Protocellsmentioning
confidence: 99%
“…To this end, we fabricated novel semi-permeable photoresponsive protocells via the encapsulation and activation of metallized peptide/porphyrin (I4K2/TPPS/Pt) fibrils within silica nanoparticle-stabilized colloidosomes capable of exhibiting a range of biomimetic and cell-like functions such as membrane gating, 10 enzyme-induced small molecule signaling, 11 in situ gene expression, 12 enzyme-mediated catalysis, 10,12,13 capsule growth and division, 14 and enzyme-directed secretion of an extracellular-like matrix. 15 Encapsulation of the photoactive I4K2/TPPS/Pt complex within the colloidosomes produced photoresponsive protocells that exhibited efficient coordination of light capture and electron transfer as demonstrated by the conversion and storage of day light (700 lux) into chemical energy in the form of NADH production within the colloidosomes. aqueous dispersion of I4K2/TPPS/Pt nanofilaments.…”
mentioning
confidence: 99%
“…[6][7][8] Biomolecules such as genetic polymers and enzymes were encapsulated into the nanoparticle-stabilized aqueous droplets (water-in-oil Pickering emulsions [9][10][11][12], and the silica membrane was cross-linked in oil to produce colloidosomes in the form of robust, semi-permeable microcapsules that could be transferred into water. 6 A range of protocellular functions were subsequently demonstrated, including in situ gene expression, 6 enzyme-mediated catalysis, 6,8,13 microcapsule growth and division, 7 membrane gating, 8 enzymedirected secretion of an extracellular-like matrix, 14 and enzyme-induced small-molecule signalling. 15 The above studies, along with diverse investigations on alternative protocell models, [16][17][18][19][20][21][22][23][24] have focused primarily on the integration of functional components into individual microcompartmentalized constructs.…”
Section: The Spontaneous Assembly Of Micro-compartmentalized Colloidamentioning
confidence: 99%